(untitled) (Research, Society and Development, 2021)
Jelly is considered a prominent product on an industrial scale, due to its good acceptance by consumers. The aim of this study was to develop conventional and mixed dietary jelly from umbu and mandacaru. The jellies were made using the standard and dietary formulation, one with sucrose and the other with xylitol, pulp of umbu and mandacaru, citric pectin and citric acid. After 30 days of storage in the environment, the physicochemical parameters were evaluated. The results obtained were subjected to analysis of variance by the Agroestat software. The average values of the physicochemical characteristics of the fruits of umbu and mandacaru obtained satisfactory values for jelly production. Conventional jelly falls within the aspects of the legislation in force. The diet jelly did not meet the identity and quality standards and showed the presence of syneresis.